Soluble recombinant protein production in Pseudoalteromonas haloplanktis TAC125 - Giuliani, Maria; PARRILLI, ERMENEGILDA; Sannino, Filomena; Apuzzo, Gennaro; MARINO, GENNARO; TUTINO, MARIA LUISA (Humana Press, 2015)
Solubility/activity issues are often experienced when immunoglobulin fragments are produced in conventional microbial cell factories. Although several experimental approaches have been followed to solve, or at least minimize, the accumulation of the recombinant proteins into insoluble aggregates, sometimes the only alternative strategy is changing the protein production platform. In this chapter we describe the use of Antarctic bacterium Pseudoalteromonas haloplanktis TAC125 as host of choice for the production of the heavy-chain antibody fragment VHHD6.1. Combining the use of a regulated psychrophilic gene expression system with an optimized fermentation process in defined growth medium, we obtained the recombinant VHHD6.1 in fully soluble form and correctly translocated into host periplasmic space.